REVIEW OF STOCK PRICE OF BHARTI AIRTEL LIMITED WITH STOCK OPTION ANALYSIS - Sharma, Sanjay Kumar; Chand, Tek (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Telecom industry in India, at present, is being run by companies which can be counted on finger tips. The two largest players in this industry in India are well known names, Bharti Airtel and Jio. Competition is growing to grab more and more market share out of the existing users as well as the potential users who would be joining digital revolution of the country. Besides, the telecom sector faces challenges from fast changing technology as also stiff government regulations. This study will take care of the overall analysis of past performance of Bharti Airtel stock to assess the stock as a good investment in the market. Our study has indicated that Bharti Stock is a win case for shorter term as well as longer term investment. Apart from this, simple option strategy has worked wonders for this stock and the results have shown that the stock is profitable even in the derivatives segment in which one out of every ten traders is having losses (SEBI,2023). The secondary data for the selected time frame has been obtained from reliable published sources, complied carefully and analysed for the study. Data analysis has been made using excel software and the IBM SPSS software.